Paracrine HB-EGF signaling reduce enhanced contractile and energetic state of activated decidual fibroblasts by rebalancing SRF-MRTF-TCF transcriptional axis - Afzal, Junaid; Du, Wenqiang; Novin, Ashkan; Liu, Yamin; Wali, Khadija; Murthy, Anarghya; Garen, Ashley; Wagner, Gunter; Kshitiz, (Frontiers in Cell and Developmental Biology, 2022)
Multiple parallels exist between placentation and cancer dissemination at molecular, cellular, and anatomical levels, presenting placentation as a unique model to mechanistically understand the onset of cancer metastasis. In humans, interaction of placenta and the endometrium results eventually in deep invasion of placental extravillous trophoblasts (EVTs) into the maternal stroma, a process similar to stromal trespass by disseminating carcinoma cells. In anticipation of implantation, endometrial fibroblasts (ESFs) undergo a process called decidualization during the secretory phase of the menstrual cycle. Decidualization, among other substantial changes associated with ESF differentiation, also involves a component of fibroblast activation, and myofibroblast transformation. Here, using traction force microscopy, we show that increased cellular contractility in decidualized ESFs is reversed after interaction with EVTs. We also report here the large changes in energetic state of ESFs upon decidualization, showing increased oxidative phosphorylation and mitochondrial competency, as well as enhanced glycolysis, presenting mechanical contractility and energetic state as new functional hallmarks for decidualization. These energetic changes, and increased ATP generation accompanied the marked increase in contractile force generation in decidualization were reduced in the presence of EVTs. We also show that increase in decidual contractility and mechanical resistance to invasion is achieved by SRF-MRTF transcriptional activation. Furthermore, we show that EVT induced paracrine secretion of HB-EGF, a potent MAPK activator, shifts the balance of SRF association from MRTF to TCF based transcription, reducing decidual ESF contractility and mechanical resistance to placental invasion. Our results identify a new axis of intercellular communication in the placental bed modulating stromal force generation and resistance to invasion with concurrent downregulation of cellular energetics. These findings have important implications for implantation related disorders, as well as stromal control of cancer dissemination.